P29-08 Development of a novel in vitro platform for the detection of profibrotic compounds based on primary human alveolar epithelium - E. Pira; G. Arib; B. Boda; S. Huang; S. Constant (Toxicology Letters, 2025)

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

Heavy rains control the floating macroplastic inputs into the sea from coastal Mediterranean rivers: A case study on the Têt River (NW Mediterranean Sea) - M. Laverre; P. Kerhervé; M. Constant; L. Weiss; B. Charrière; M. Stetzler; D. González-Fernández; W. Ludwig (Science of The Total Environment, 2023)

Calcifediol is a safe and effective metabolite for raising vitamin D status and improving growth and feed conversion in rainbow trout - S. Rider; V. Verlhac-Trichet; D. Constant; E. Chenal; S. Etheve; B. Riond; H. Schmidt-Posthaus; R. Schoop (Aquaculture, 2023)

Comparison of reproductive performances of local and improved pigs reared in south Benin - Ignace Ogoudanan Dotché; Constant B. O. Bankolé; Mahamadou Dahouda; Rodrigue Biobou; Gabriel A. Bonou; Nicolas Antoine-Moussiaux; Jean-Paul Dehoux; Pierre Thilmant; Guy Apollinaire Mensah; Benoît G. Koutinhouin; Issaka Youssao Abdou Karim (Tropical Animal Health and Production, 2020)

Unconjugated Bilirubin Restricts Oligodendrocyte Differentiation and Axonal Myelination - Andreia Barateiro; Veronique E. Miron; Sofia D. Santos; João B. Relvas; Adelaide Fernandes; Charles ffrench-Constant; Dora Brites (Molecular Neurobiology, 2013)

DDT resistance in Drosophila correlates with Cyp6g1 over-expression and confers cross-resistance to the neonicotinoid imidacloprid - P. Daborn; S. Boundy; J. Yen; B. Pittendrigh; R. ffrench-Constant (Molecular Genetics and Genomics, 2001)

Analysis of some morphological and biochemical characteristics of the egg of the predaceous bugMacrolophus caliginosus (Het.: Miridae) during embryogenesis - B. Constant; S. Grenier; G. Bonnot (BioControl, 1994)